Chinese elderly migrants' loneliness, anxiety and depressive symptoms: The mediation effect of perceived stress and resilience - Hao Wang; Yanjie Hou; Lin Zhang; Man Yang; Ruyue Deng; Jun Yao; Jun Yao; Jun Yao (Frontiers Media S.A., 2022)
Elderly migrants who face the dual challenges of aging and migration are more likely to suffer psychological disorders. Existing research has demonstrated a link between loneliness and psychological disorders in the general elderly population. However, we know little about the relationships among elderly migrants, and the psychological mechanisms linking them. This study aims to examine the effects of loneliness on anxiety and depressive symptoms among Chinese elderly migrants, and explore the mediating roles of perceived stress and resilience. All 654 participants were recruited in Nanjing, Jiangsu Province, China. Results showed that loneliness was significantly correlated with anxiety and depressive symptoms (p < 0.001). Perceived stress and resilience mediated the relationship between loneliness and anxiety symptoms. The mediating effect of perceived stress was 0.128 (Bootstrap 95% CI: 0.092-0.168, Ratio = 37.4%). Resilience was 0.026 (Bootstrap 95% CI: 0.005-0.049, Ratio = 7.6%). Furthermore, perceived stress and resilience also mediated the relationship between loneliness and depressive symptoms. The mediating effects were 0.111 and 0.043, respectively (Bootstrap 95% CI: 0.073-0.151, Ratio = 27.9%; Bootstrap 95% CI: 0.020-0.069, Ratio = 10.8%). All the mediating effects were significant because the bootstrap 95% CIs did not contain zero. Overall, our findings suggested that loneliness not only can directly influence elderly migrants' anxiety and depressive symptoms but also by increasing perceived stress or decreasing resilience.